2020
DOI: 10.1155/2020/2073803
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Differential Urinary Metabolites after High-Intensive Training in Teenage Football Players

Abstract: Objective. The mechanism underlying the fatigue of football players is closely related to the energy depletion and accumulation of metabolites; the present study tries to explore the metabolic mechanism in teenage football players during exercise-induced fatigue. Methods. 12 teenage football players were subjected to three groups of combined training by using a cycle ergometer, with the subjective Rating of Perceived Exertion (RPE) as a fatigue criterion. The following indicators were measured in each group af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…It was reported that repeated exhaustive exercise induced fatigue could bring about oxidative damage to the mitochondrial membrane, 33 while glycerophospholipids could maintain the structure of mitochondrial membrane to restore function. In addition, acute high‐intensity exercise could change glycerophospholipid metabolism, which further affecting the function of the cell membrane 34 . It was observed that glycerophospholipid levels would be altered in inflammatory bowel disease (IBD) patients with fatigue 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that repeated exhaustive exercise induced fatigue could bring about oxidative damage to the mitochondrial membrane, 33 while glycerophospholipids could maintain the structure of mitochondrial membrane to restore function. In addition, acute high‐intensity exercise could change glycerophospholipid metabolism, which further affecting the function of the cell membrane 34 . It was observed that glycerophospholipid levels would be altered in inflammatory bowel disease (IBD) patients with fatigue 35 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, acute highintensity exercise could change glycerophospholipid metabolism, which further affecting the function of the cell membrane. 34 It was observed that glycerophospholipid levels would be altered in inflammatory bowel disease (IBD) patients with fatigue. 35 Glycerophospholipids, which consisted of the lipid bilayer, might play an important role to protect intestinal epithelium barrier from the destruction, thus to maintain the stable intestinal microecosystem.…”
Section: Glycerophospholipid Metabolismmentioning
confidence: 99%
“…The latter metabolite has strong antidepressant effects, and therefore, M17 is correlated with the euphoric effect of physical exercise and the therapeutic potential of the latter against depression [65]. Interestingly, 4-hydroxyphenyl acetic acid, a metabolite of M4, was shown to decrease during the intensive training of young athletes [66]. Estrone sulfate (M18) is the biotransformation product of estrone after its biotransformation by arylsulfatase.…”
Section: Biological Evaluationmentioning
confidence: 99%
“…Focusing on football, short-term changes in the metabolic profiles of young male professional players' responses revealed a significant post-exercise increase in acylcarnitines involved in fatty acid oxidation, and slight increases in purine metabolites, especially hypoxanthine and xanthine (Alzharani et al, 2020). Another study analyzing metabolic mechanisms in male teenage football players during exercise-induced fatigue reported changes in five metabolic pathways (glycine-serinethreonine metabolism, citrate cycle, tyrosine metabolism, nitrogen metabolism, and glycerophospholipid metabolism) (Cao et al, 2020). The analysis of urine metabolic profiles and EPTS data from 80 professional football male players collected in an observational longitudinal study identified changes in steroid hormone metabolites, hypoxanthine metabolites, amino acids, intermediates in phenylalanine metabolism, tyrosine, tryptophan metabolites, and riboflavin associated with the external load indicating an alteration of biochemical pathways linked to the long-term adaptation to training (Quintas et al, 2020).…”
Section: Introductionmentioning
confidence: 99%